The utilization of red dragon fruit peel extract (Hylocereus polyrhizus) in nanoemulsion as an antioxidant - Agustin, Eriska; Zahara, Ega (Faculty of Pharmacy, Universitas Pancasila, 2025)
The red dragon fruit plant (Hylocereus polyrhizus) contains bioactive substances, one of which functions as an antioxidant from anthocyanin and betacyanin. The Dragon Fruit Peel (DFP) has not been widely used by the community in the health sector, and it is only becomes waste. The preparation of nanoemulsion aims to increase the low antioxidant activity of dragon fruit peels. The preparation of DFP nanoemulsion using 8% Tween 80 as emulsifier, 1% oleic acid, and 2% transcutol, with variations in extract concentrations of 1% and 2%. The globule size is reduced to nanoemulsion using a sonicator bath for 60 minutes. The testing of antioxidant activity using the DPPH method. The results of the organoleptic test showed that the DFP extract nanoemulsion had a transparent yellow color with a globule size and Polidispersity Index (PI) of 165±5.54 nm (PI=0.2±0.03) and 115±3.46 nm (PI=0.3±0.02) at an extract concentration of 1 % and 2%. The globule morphology using TEM shows a spherical shape. The results of the pH test showed a range of 4.5-5.3. In testing the antioxidant activity, the DFP extract nanoemulsion showed an increase in IC50 values at 1% and 2% extract concentrations, namely 85.39±4.69 and 64.46±3.45, compared to the extract without formula (pure extract), namely 167.34±8.98. The DFP nanoemulsion preparations produced globule sizes in the nano range, and antioxidant activity testing showed an increase in the IC50 value of 2 concentrations compared to conventional extracts (p<0.05).